2023
DOI: 10.1007/s00464-023-09997-6
|View full text |Cite
|
Sign up to set email alerts
|

Can endoscopic follow-up after acute diverticulitis be rationalised?

Abstract: Background Acute diverticulitis (AD) is a common cause of presentation to emergency surgical services. Follow-up with endoluminal investigation to exclude colorectal cancer (CRC) remains controversial. Guidelines are increasingly moving to a more restrictive follow-up based on severity of disease and age. The purpose of this observational study was to assess the prevalence of CRC in AD patients and the impact of follow-up on endoscopy services. Methods Patients admitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…Wheat et al concluded that white women undergo more hospitalizations due to diverticular disease [ 13 ]. While earlier studies showed that men were affected more, recent studies have reported that the incidence of diverticular disease is also getting high in women.…”
Section: Reviewmentioning
confidence: 99%
“…Wheat et al concluded that white women undergo more hospitalizations due to diverticular disease [ 13 ]. While earlier studies showed that men were affected more, recent studies have reported that the incidence of diverticular disease is also getting high in women.…”
Section: Reviewmentioning
confidence: 99%